2018
DOI: 10.3171/2018.10.focusvid.18240
|View full text |Cite
|
Sign up to set email alerts
|

Awake craniotomy for a cavernous angioma in the Broca’s area

Abstract: Cavernous angiomas constitute 5%–10% of cerebrovascular malformations and may cause seizure and neurological deficits from bleeding.4 The authors present a case of a 44-year-old man with a 3.5-year history of epilepsy without complete seizure control despite anticonvulsants. Brain MRI showed a 2.8 cm cavernous angioma at the left pars opercularis, also known as the Broca’s area.3 The patient underwent an awake craniotomy for intraoperative cortical–subcortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“… 5 Positive outcomes were also observed in patients with cavernous malformations and epidermoid cysts; AC resulted in complete recovery of affected functions. 26 , 28 , 29 In addition, AC procedures also score highly on patient satisfaction. A Brazilian study of 17 patients found that 88% held the surgery in a positive light, and preoperative apprehensions of possible paralysis and serious neurological deficits were assuaged.…”
Section: Ac In South America: Practice Outcomes and Recent Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 Positive outcomes were also observed in patients with cavernous malformations and epidermoid cysts; AC resulted in complete recovery of affected functions. 26 , 28 , 29 In addition, AC procedures also score highly on patient satisfaction. A Brazilian study of 17 patients found that 88% held the surgery in a positive light, and preoperative apprehensions of possible paralysis and serious neurological deficits were assuaged.…”
Section: Ac In South America: Practice Outcomes and Recent Advancesmentioning
confidence: 99%
“…Numerous studies conducted in the region have demonstrated how AC practices lead to reduced levels of post-operative morbidity and mortality. 10 , 26 , 28 , 29 Traditionally, greater rates of postoperative complications following conventional and antiquated neurosurgical procedures have led to the premature withdrawal of patients from the labour market, which has significant impacts on the overall economic well-being of the country. 27 , 31 , 32 Thus, by reducing the overall levels of postoperative complications, AC ensures that patients can return to their normal lives and livelihoods much quicker than usual and can contribute to the economic prosperity of the country.…”
Section: Ac In South America: Practice Outcomes and Recent Advancesmentioning
confidence: 99%
“…Hence, meticulous planification of surgery, including cortico-subcortical intraoperative brain stimulation (ioBS) in the awake patient, also known as awake brain mapping, has been advised so that the less hazardous approach to cavernoma could be chosen. 1,4,5 Intraoperative language mapping under local anaesthesia has been probed to minimize the risk of postoperative language deficit 6,7 in brain tumour patients. Nevertheless, not only language-related functions but other higher functions, including visuospatial cognition, sociocognitive functions and executive functions can be tested intraoperatively by means of ioBS 8,9 thus contributing to improve postoperative clinical outcome and quality of life.…”
Section: Introductionmentioning
confidence: 99%